The Effect of Environmental Financial Accounting Practices on the Cost of Capital in Public Companies Listed on the Indonesia Stock Exchange - Sari Dewi; Natalia Harini (Jurnal Mantik, 2021)
This study aims to identify the relationship between the Level of Environmental Financial Accounting Practices (EFAP) and the Cost of Capital. The audit results from the financial statements and the Sustainability Report from the 2016 – 2019 period are secondary data used in the research. Fulfillment of the criteria to be used as a research sample amounted to 56 companies which were then tested using the Eviews 10 program. The study proved that company size (SIZE) had a significantly negative effect on the Cost of Equity Capital. Market to Book Ratio (MTB), Return on Assets (ROA), Cash Flow Operations (CFO), Cash Ratio (CR), and Net Loss (LOSS) have no significant effect on the Cost of Equity Capital. Company size (SIZE), Leverage (LEV), and Net Loss (LOSS) have a significant effect on the Cost of Debt Capital in addition, Environmental Financial Accounting Practices (EFAP), Market to Book ratio (MTB), Return on Assets (ROA), Cash Flow Operations (CFO), and Cash Ratio (CR) have no significant effect on the Cost of Debt Capital.